BUILDING WORD-OF-MOUTH IN EDUCATIONAL TOURISM DESTINATIONS: THE ROLE OF MEDIATION PERCEIVED VALUE AND TOURIST SATISFACTION - Suryaningsih, Ika Barokah; Sumani, Sumani; Haqi, Roikha Nurul; Putri, Rizky Atika Salsabila Ivabianca (Unitri Press, 2023)
This research aims to examine the mediating role of perceived value and tourist satisfaction on the influence of the destination's image on word of mouth at Blitar Chocolate Village as an educational tourism destination. This explanatory research used incidental sampling techniques to determine tourist respondents who were on educational tour visits as many as 130 people. The data is analyzed using partial least squares (PLS) with SmartPLS 4.0 software to analyze the data.. As a result, Perceived value is not able to mediate the image of the destination to word of mouth, but tourist satisfaction is able to mediate the image of the destination to word of mouth Blitar Chocolate Village. For further research, other variables can be added to find out updates and developments regarding factors that can affect perceived value, tourist satisfaction, and word of mouth.